Continuity of care for orthopaedic patients in a district general hospital - Kulloo, Praneta (BMJ Qual Improv Rep, 2014)
Continuity of care has been defined as a patient repeatedly consulting the same doctor and forming a therapeutic relationship. There is evidence that not only do patients value continuity of the care they receive but also that provider continuity is related to lower overall total healthcare costs and better healthcare outcomes. A retrospective audit was undertaken in James Paget Hospital, a district general hospital in East Anglia, England, to assess continuity of care from the preoperative clinic to surgery and subsequent postoperative follow-up in the orthopaedic department. Overall continuity of care by individual surgeon was 23% and by orthopaedic team (consultant and middle grade staff) 43% in the first audit cycle of 106 patients in 2008. In the second cycle in 2010, this improved to 24% and 56%, respectively, in a sample of 156 patients. Moreover, the continuity of care for trauma patients improved from 10% to 75%. Interventions which resulted in the improvement were change of on-call rota and the implementation of measures so that, following surgery, patients were allocated to the operating surgeon's clinic postoperatively. This completed audit cycle highlights the importance of continuity of care of patients and how efficient management led to a more patient centred delivery of healthcare.